Ethyl cyanoacrylate reinforced polyvinylidene fluoride separators for robust lithium ion batteries. (25th January 2021) - Yang, Mengqiu; Liu, Yuanpeng; Yuan, Botao; Guang, Zhaoxu; Liu, Jipeng; Dong, Liwei; Ji, Yuanpeng; Li, Qun; Liang, Yifang; Dong, Yunfa; Hao, Sue; Yang, Chunhui; et al.
Abstract : Herein a composite separator is proposed to realize high mechanical strength, high thermal stability and high electrolyte wettability by incorporating ethyl cyanoacrylate (ECA) into polyvinylidene fluoride (PVDF). Abstract : Ideal separators of Li-ion batteries should possess key characteristics simultaneously, including high mechanical strength, high thermal stability and high electrolyte wettability. Herein a composite separator is proposed to realize these properties by directly incorporating ethyl cyanoacrylate (ECA) into a polyvinylidene fluoride (PVDF) polymer matrix. With significantly enhanced mechanical strength resulting from abundant hydrogen bonds in ECA and van der Waals forces between ECA and PVDF, the ECA–PVDF separator possesses high thermal tolerance and superior capability for electrolyte uptake. The half cell with a LiFePO4 cathode and ECA–PVDF composite separator delivers a high discharge capacity of 154.1 mA h g −1 with 98.4% capacity retention after 100 cycles at 1C (1C = 0.22 mA cm −2 ), which is attributed to the inherent structure of ECA that exhibits strong interaction with ethylene carbonate (EC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC).